Computerized image analysis of iron-stained macrophages - Gente, Karolina; Schäfer, Sebastian Markus; Mall, Marcus A.; Muckenthaler, Martina (Annals of hematology, 2013)
Analysis of iron levels in single cells is critical to understand the consequences of impaired regulation of iron homeostasis. Here we establish a method to analyze intracellular iron deposits by computerized image analysis of Prussian blue-stained alveolar macrophages as a test system. We efficiently detected small differences in macrophage steady-state iron levels in Hfe−/− mice as well as inflammation-induced iron sequestration upon lipopolysaccharide instillation. In conclusion, computerized image analysis of single cells is a robust and reproducible tool suitable for iron measurements in small sample sets with limited cell yield.